Fractured T Tube Fragment in Common Bile Duct during Retrieval: An Unforeseen Mishap - Rajput, Deepak; Patnaik, Itish; Shasheendran, Sruthi; Kumar, Beeram K. Prasanna; Gupta, Amit (The Surgery Journal, 2021)
Common bile duct (CBD) exploration by surgical method—open or laparoscopic, traditionally involved using a T tube to take care of postoperative intraluminal pressure and edema. The complications of T tube include bile leak after removal, formation of biliary fistula, excoriation of the skin, dehydration, saline depletion, retained T tube fragment, CBD obstruction, cholangitis, pancreatitis, and duodenal erosion. Here, we report a case of retained T tube fragment after an attempted removal in an operated case of choledocholithiasis, which was managed by endoscopic retrograde cholangiopancreatography and balloon catheter removal of the remnant.
Keywords: choledocholithiasis; CBD exploration; T tube fragment retrieval; ERCP